Pengaruh Penerapan E- Filling Terhadap Kepatuhan Wajib Pajak Dalam Menyampaikan SPT Tahunan Dengan Kepuasan Kualitas Pelayanan Sebagai Variabel Intervening (Studi Kasus di Badan Pengelolaan Pajak dan Retribusi Daerah Provinsi Sumatera Utara) - Nadratul Hasanah Lubis; Hendra Harmain; Nurwani Nurwani (Jurnal Riset AKuntansi dan Bisnis, 2023)
The purpose of this study is to determine the Effect of the Application of E-filling on Taxpayer Compliance with Service Quality Satisfaction as an Intervening Variability in the Regional Tax and Retribution Management Agency of North Sumatra Province. The type of research used was quantitative research with questionnaire and sample data collection techniques used by 100 taxpayer respondents at the Regional Tax and Retribution Management Agency of North Sumatra Province. Data testing techniques used in this study include Descriptive Statistical Analysis, Classical Assumption Test, Simple Linear Regression Test, Path Analysis Test, Sobel Analysis, R Square Test, and t Test. The results of this study show that the Application of E-filling has a positive and significant effect on Taxpayer Compliance 0.000 0.05, the Application of E-filling has a positive and significant effect on Taxpayer Compliance with Service Quality Satisfaction as an intervening variable. Path Analysis Test Results Indirect The application of E-filling (X) through Service Quality (Z) has a significant influence on taxpayer compliance (Y). Service Quality Satisfaction is able to mediate the relationship between the Application of E-filling to Taxpayer Compliance.